The vestibular implant: effects of stimulation parameters on the electrically-evoked vestibulo-ocular reflex - van Boxel, Stan C. J.; Vermorken, Bernd L.; Volpe, Benjamin; Guinand, Nils; Perez-Fornos, Angélica; Devocht, Elke M. J.; van de Berg, Raymond (Frontiers in Neurology, 2024)
Introduction The vestibular implant is a neuroprosthesis which offers a potential treatment approach for patients suffering from vestibulopathy. Investigating the influence of electrical stimulation parameters is essential to improve the vestibular implant response. Optimization of the response focuses on the electrically evoked vestibulo-ocular reflex. It aims to facilitate high peak eye velocities and adequate alignment of the eye movement responses. In this study, the basic stimulation parameters of the vestibular implant were tested for their effect on the electrically evoked vestibulo-ocular reflex. Methods Four stimulation parameters, including the stimulation amplitude, phase duration, stimulus rate and speed of change of stimulation, were systematically tested in a cohort of nine subjects with a vestibulo-cochlear implant. These parameters were tested to evaluate their effect on fitting settings (i.e., threshold of activation, upper comfortable limit and dynamic range) as well as on the electrically evoked vestibulo-ocular reflex (peak eye velocity and alignment). Results It was confirmed that, in addition to current amplitude, the peak eye velocity of the response can be increased by increasing the phase duration and pulse rate. Both parameters have little effect on the alignment of the eye response. However, a longer phase duration decreased the range between the threshold of activation and the upper comfortable limit of the electrical stimulation (i.e., dynamic range). Furthermore, these results show that next to the amplitude of the stimulation, the speed of change in stimulation has a determinative positive effect on the peak eye velocity. Conclusion The observations in this study imply that the vestibular implant response, in terms of peak eye velocity, can be optimized with a higher pulse rate and longer phase duration. However, this comes at a trade-off between the dynamic range and power consumption. This study provides essential insights for fitting strategies in future vestibular implant care.